THE EFFECT OF MURABAHAH, MUDHARABAH AND IJARAH EARNINGS UPON THE PROFIT OF BANK BRI SYARIAH, BRANCH OFFICE SUKABUMI - Dwi Gemina; Dedy Supriyadi (STIE Binaniaga, 2018)
The purposes of this research are: 1) Analysing the development of murabahah, mudharabah and ijarah earnings at PT Bank BRI Syariah, Branch Office Sukabumi; 2) Analysing the effect of murabahah, mudharabah and ijarah earnings simultaneously upon the profit of PT Bank BRI Syariah Branch Office Sukabumia: 3) Analysing the effect of murabahah, mudharabah and ijarah earnings partially upon the profit of PT Bank BRI Syariah Branch Office Sukabumi. Research method has applied associative research method. Research data has applied financial data of PT Bank BRI Syariah Branch Office Sukabumi for the periode of 2014 up to 2015 using classical assumption test, multiple regression, F test and T test. Result of the research has determined that overall murabahah, mudharabah and ijarah earnings have been increasing. In 2015 earnings increasing had reached 125 % more than the previous year and the most contribution is given by murabahah earnings. Variable of murabahah earnings, mudharabah earnings and ijarah earnings simultaneously have been affecting positively and significantly the Profit. And partially murabahah and ijarah earnings have positively and significantly affected the profit, nevertheless, variable of mudharabah earnings has not affected significantly the profit.Keywords : Murabahah earnings, Mudharabah earnings, Ijarah earnings, profit Bank BRI Syariah, Branch office Sukabumi.